The Eagle has Flown - Higgins, Jack 1929-; Page, Michael (Grand Haven, MI Brilliance Audio, 2010)
IRA assassin Liam Devlin returns to Britain in an attempt to effect the escape of German soldier Kurt Steiner from the Tower of London and return with him to Berlin.
Unabridged.
Compact discs.
Read by Michael Page.
Keywords: World War, 1939-1945 -- Fiction -- Secret service -- Germany; Audiobooks; Germany -- Fiction; War stories; Spy stories